Effectiveness of ”Camerunis” cookies made from functional ingredients as a healthy snack to prevent degenerative diseases - Slamet Iskandar; Latsmi Wayansari; Idi Setiyobroto; Diana Andriyani Pratamawati (AcTion: Aceh Nutrition Journal, 2024)
The consumption of monster cookies and dessert boxes can be detrimental to health. This study produces cookies from a mixture of functional ingredients such as wheat flour, mocaf, brown rice, and cinnamon, which are named Camerunis Cookies as an alternative to healthier cookies that prevent degenerative diseases such as Diabetes Mellitus.  This study aimed to determine the nutritional value, glycemic index, and antioxidant activity of Camerunis cookies as well as their effect on their impact in the prevention of degenerative diseases (DM) in experimental animals. Blood glucose levels in experimental animals. The research method used was a quasi-experimental design. The number of samples was 15 white male rats divided into 3 groups, namely normal rats, diabetic rats without giving and diabetic rats by giving Camerunis Cookies.  Camerunis Cookies were produced in the Food Laboratory of Poltekkes Kemenkes Yogyakarta. Proximate, glycemic, antioxidant, and blood glucose levels were tested in experimental animals at  the laboratory of Pusat Antar Universitas (PAU) UGM Yogyakarta. The research data were descriptively analyzed. The moisture content of the C. cookies was 2,18%, ash content of 1,95%, and 6,40%, respectively. fat 31,74%. carbohydrates (57,72%), the glycemic index (35 IG), and antioxidants (27,6 µg/mL. The average reduction in blood glucose levels in the DM rats was 41,55 mg/dL per week. In conclusion, Camerunis cookies meet the SNI 01-2973-1992 standards, have a low glycemic index, contain strong antioxidants, and can reduce blood glucose levels in DM rats.